Hope as a Unique Agent of Resilience in Socio-economically Disadvantaged Adolescents - Zeynep Aydın Sünbül; Ferah Çekici (Institute of Advanced Engineering and Science, 2018)
The aim of this study was to explore the predictive effect of hope for resilience in socio-economically disadvantaged adolescents. Participants of the study were 692 (395 female, 297 male) students attending to 9th, 10th and 11th grades. The age range of the sample was 14-19 (M = 16.24, SD=.89). A convenient sampling was used to select the participants who are picked from four high schools located in low income regions. In order to collect data, The 14-Item Resilience Scale (Wagnild, 2010) and Dispositional Hope Scale (Snyder et al., 1991) were used as data collection instruments. The predictive effect of hope on resilience was analyzed through linear regression. Regression analysis yielded that hope explains 48% of the variance in the resilience scores of participants. This result indicates that hope is a powerful significant predictor of resilience for socio-economically disadvantaged adolescents.